CER: The cornerstone of New Zealand's trade policy - Chris Nixon (New Zealand Institute of Economic Research (NZIER), 2000)
In a small open economy heavily dependent on trade, such as New Zealand, small changes in New Zealand's international trading environment have major impacts on economic well-being. The simple fact is that small countries are far more vulnerable to economic change than large countries. To progress, make the best use of its resources and overcome their natural disadvantages, smaller nations need to foster an efficient economic environment. An efficient trade policy is an important part of any small country's economic policy and is a vital component for improving the standard of living. So the simple answer to why economists are interested in trade policy, particularly in a small open economy, is that we want the most efficient structure possible. That leads neatly on to why CER is important to New Zealand. It is not just because Australia is the closest most important market, but: [1] The Agreement has an efficient structure. [2] It is economically logical. [3] It is consistent and seamless with other trade policies that New Zealand wishes to follow. This paper, funded by the Foundation of Research Science and Technology, is part of a wider suite of papers looking at trade. Its focus is trade policy and represents work in progress.
Keywords: 330; Internationale Wirtschaftsbeziehungen; Außenhandelsliberalisierung; Neuseeland; Australien